Analisis Faktor-Faktor Pelatihan Kerja Terhadap Peningkata Prestasi Kerja Karyawan Pada Bumdes di Karangasem - Tias Suprapto Putri; Putu Ari Mulyani; I Made Arjana (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study aims to find out how much influence Job Training has on employee Work Performance in Bumdes in Karangasem. This type of research uses quantitative research. Data collection used interview, observation, and questionnaire methods filled out by 56 Bumdes employees. The analysis technique used is Multiple Linear Analysis which is carried out using the IBM SPSS Statistics 24.0 program. Training factors consisting of trainer abilities, training materials, training methods, training facilities, and management commitment partially have a significant influence on employee work performance in Bumdes in Karangasem Regency. This conclusion is based on the t-counting results of variable X1 of 2.806, variable X2 of 2.171, variable X3 of 2.166, variable X4 of 2.343, and variable X5 of 2.221. The trainer's ability variable has the most dominant influence on employee work performance in Bumdes in Karangasem Regency. This conclusion is based on the test results of the Regression coefficient ?1 (trainer ability variable) where variable X1 has a value greater than other variables of 0.204